Donepezil-induced response of Spirulina supplemented rat urinary bladder - (:unkn) unknown (COMENIUS UNIV, 2013)
Objective: At present, very little is known about the effects of donepezil on vascular reactivity. The aim of the present study was to evaluate the responses of rat urinary bladder to donepezil (10(-10)-3x10(-4) M) and the role of Spirulina supplementation in these effects. Material and methods: Animals were divided into the two groups of six animals in each group. The first group received only distilled water daily as vehicle for six weeks and served as the control. The second group received Spirulina 750 mg kg (-1) orally, daily for six weeks and served as the spirulina group. Preparations of rat urinary bladder were used from both groups. Results: Donepezil produced concentration dependent relaxation of rat urinary bladder preparations pre-contracted with KCl. The pIC(50) value, but not the maximal response of donepezil, was significantly lower (p<0.05) in the Spirulina supplemented group. Conclusions: These results demonstrated for the first time that spirulina treatment can affect urinary bladder activity (Fig. 1, Ref. 20). Full Text in PDF www.elis.sk.
Keywords: donepezil; rat; Spirulina; urinary bladder